2010
DOI: 10.1111/j.1601-0825.2010.01713.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Skp2 expression and nodal metastasis in Stage I and II oral squamous cell carcinomas

Abstract: Correlation between Skp2 expression and nodal metastasis in stage I and II oral squamous cell carcinomas / Tosco P; La Terra Maggiore GM; Forni P; Berrone S; Chiusa L; Garzino-Demo P. The aim of this study was to investigate the role of S-phase kinase associated protein (Skp2) in the development of nodal metastasis and to assess its influence on prognosis in stage I and II oral squamous cell carcinomas (OSCCs). Experimental Design: Seventy-one patients affected by OSCC (stage I-II) were observed in the period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Moreover, high expression of Skp2 is correlated with tumour recurrence in human cancers (Einama et al , 2006). Furthermore, the positive relationship between Skp2 expression and tumour metastasis has been reported in human malignancies (Tosco et al , 2011). Notably, Skp2 overexpression was detected more frequently in tumours metastatic to the lymph nodes in breast cancer (Zheng et al , 2005).…”
mentioning
confidence: 83%
“…Moreover, high expression of Skp2 is correlated with tumour recurrence in human cancers (Einama et al , 2006). Furthermore, the positive relationship between Skp2 expression and tumour metastasis has been reported in human malignancies (Tosco et al , 2011). Notably, Skp2 overexpression was detected more frequently in tumours metastatic to the lymph nodes in breast cancer (Zheng et al , 2005).…”
mentioning
confidence: 83%
“…Recently, it has been reported that Skp2 expression correlated significantly with histological grade and tumor size in human hepatocellular carcinoma [44]. Moreover, a correlation between elevated Skp2 protein expression and tumor metastasis has been noted in multiple tumors, including melanoma [35], oral squamous cell carcinomas [45], pancreatic cancer [46], and breast carcinoma [47]. Furthermore, Skp2 expression has been discovered to predict for poor prognosis in breast cancer [47], melanoma [35], and nasopharyngeal carcinoma [36].…”
Section: Skp2 Is a Bona Fide Proto-oncoproteinmentioning
confidence: 99%
“…Similarly, Skp2 expression was correlated with histological grade and tumor size in hepatocellular carcinoma (Lu et al, 2009). Moreover, elevated Skp2 expression is related with tumor metastasis in melanoma (Rose et al, 2011), lymphoma, oral squamous cell carcinomas (Tosco et al, 2011), pancreatic cancer (Einama et al, 2006), and prostate cancer (Wang et al, 2011a). Furthermore, Skp2 expression has been considered as a biomarker for poor prognosis in breast cancer (Voduc et al, 2008), melanoma (Rose et al, 2011), and nasopharyngeal carcinoma (Xu et al, 2011).…”
Section: Skp2 Is a Proto-oncoproteinmentioning
confidence: 99%
“…Many studies have shown the positive relationship between Skp2 expression and tumor metastasis in human cancers (Tosco et al, 2011). For example, Tosco et al (2011) found the correlation between Skp2 expression and nodal metastasis in oral squamous cell carcinomas.…”
Section: The Role Of Skp2 In Development and Progression Of Breast Camentioning
confidence: 99%
See 1 more Smart Citation